Designing instructional module for learning Arabic using augmented reality - Nordin, Fitri Nurul’Ais; Md Ghalib, Mohd. Feham; Sahrir, Muhammad Sabri (Centre for Global Open Access Learning - Immersive Technology & Quality Assurance (GOAL-ITQAN), Universiti Sains Islam Malaysia (USIM), 2017)
Highlights:The research aims to design an instructional module for learning Arabic using Augmented Reality. This research employs analytical and descriptive methods, by reviewing documents, prospectus and scientific magazines printed at the university. In addition, this research relies on other researches, books and scientific journals. The researcher use ADDIE Model to develop the module as it is simple and suitable form of instructional design modules in learning Arabic. In order to review the module, a number of experts has evaluated the completed module to evaluate the quality of the module and technical parts. The researcher has applied the module of learning Arabic using Augmented Reality to 53 students and distributed questionnaires of formative evaluation to the respondents. Through the questionnaire, the researcher found that 88.7% of the students believed that the module of learning Arabic using Augmented Reality is able to motivate student to learn Arabic. Therefore, the research encounters several results at the end of its analysis, including: using Augmented Reality in learning will increase learning motivation of the learner, and compensate the lack of resources in teaching and learning, reduce the cost as well as provides learning language skills without depending on other teaching aids which contains videos, and three-dimensional shapes (3D), audios and data. The researcher also listed some suggestions which can be used in the development of module design for learning and teaching Arabic language.